Quantitative syntax analysis - Köhler, Reinhard 1951- (Quantitative linguistics, 2012)
This is the first book to bring together the fields of theoretical and empirical studies in syntax on the one hand and the methodology of quantitative linguistics on the other hand. An introduction into the aims and methods of the quantitative approach to linguistics in general and to syntax in particular prepares the reader for the following chapters, which inform about measurement and data acquisition methods and the most common mathematical models for the analysis of syntactic and syntagmatic material. Various examples illustrate how these models are applied and show the corresponding results. Reinhard Köhler, Universität Trier, Germany